2020
DOI: 10.4103/jfmpc.jfmpc_369_20
|View full text |Cite
|
Sign up to set email alerts
|

Motivators and barriers to research among doctors in the Indian medical scenario: A cross-sectional study from Karnataka, India

Abstract: Background: The fundamental principles of healthcare practices and policies are derived from good quality research. Doctors collectively are a source of vast sums of invaluable information. This information if effectively utilized can improve and strengthen the healthcare system. Our study provides a comprehensive overview of the ecosystem of an Indian medical researcher. Objectives: To understand (1) the obstacles faced by medical professionals (2) the challenges encou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Residents found the elements of statistical analysis and sample size as difficult tasks, with 36.48% having little understanding of them. 16 Another study showed that medical students had moderate knowledge of biostatistics, with 75% of them saying they were unable to read and write the statistical portion of a research paper. 17…”
Section: P R O V I S I O N a L L Y A C C E P T E D F O R P U B L I C ...mentioning
confidence: 99%
“…Residents found the elements of statistical analysis and sample size as difficult tasks, with 36.48% having little understanding of them. 16 Another study showed that medical students had moderate knowledge of biostatistics, with 75% of them saying they were unable to read and write the statistical portion of a research paper. 17…”
Section: P R O V I S I O N a L L Y A C C E P T E D F O R P U B L I C ...mentioning
confidence: 99%
“…Many health research institutions in sub-Saharan African countries do not have basic access to information communication technology infrastructure, internet connectivity and library facilities (27). Similarly, time limitations in research participation in both men and women has been well-documented in other LMICs (25,37,41,44) and also some HICs (25,45,46). Mentors, local and international collaboration, and the desire to solve problems emerged as facilitators in our study for engagement in conducting research, similar to other studies (17,39,(47)(48)(49).…”
Section: Regression Model On Factors In Engagement In Researchmentioning
confidence: 99%
“…It is heartening to note that most doctors who pursued research did it for personal interest and recognition rather than just monetary benefits. [ 15 ] The significant challenges in performing pertinent and methodical research are lack of knowledge, lack of mentor/guide, and other resources like access to journals and funding. A medical student echoed similar challenges.…”
Section: R Esearch In I Ndian M Edical S Chools : O mentioning
confidence: 99%